Договір перевезення пасажира: теорія та практика забезпечення прав пасажира - Самойленко, Георгій Валерійович; Самойленко, Георгий Валерьевич; Samoylenko, Georigiy V. (My University, 2021)
Дисертація на здобуття наукового ступеня доктора юридичних наук за спеціальністю 12.00.03 – цивільне право і цивільний процес; сімейне право; міжнародне приватне право. – Національний університет «Одеська юридична академія». Одеса, 2021. Дисертація є першим у вітчизняній науці цивільного права комплексним дослідженням теоретичних і практичних проблем забезпечення прав пасажира за договором перевезення пасажира в умовах глобалізації та євроінтеграційних процесів, на підставі якого розроблено концепцію їх цивільно-правового забезпечення. У дисертації визначено методологічні засади дослідження та надано характеристику правового регулювання договірних відносин з перевезення пасажира як одного із способів здійснення права на свободу пересування, забезпечення прав пасажира в сучасних цивілізаційних умовах. Надано правову характеристику правовідносин з перевезення пасажира та визначено їх структуру. Аргументовано споживчий характер правовідношення з перевезення пасажира, представницький характер відносин між перевізником і іншими учасниками правовідносин з перевезення пасажира. Надано правову характеристику правовідносин на основі використання мобільних додатків на основі платформ Uber та BlaBlaCar. Встановлено особливості механізму правового регулювання перевезень пасажирів та надано характеристику його елементів, нормативно-правового та договірного регулювання перевезення пасажира, співвідношення актів цивільного, транспортного та споживчого законодавства в регулюванні цих відносин та забезпечення прав пасажира. Встановлено особливості правового регулювання відносин з перевезення пасажирів в ЄС. Визначено правове становище пасажира як сторони договору та споживача транспортних послуг в концепті права на безпеку. Визначено права пасажира, визнані та ті, які потребують визнання та правової охорони, запропоновано цілісний підхід до формування ефективного механізму забезпечення прав пасажира. Особлива увага приділена гарантіям забезпечення прав пасажира, наслідкам порушення його прав, їх цивільно- правового захисту, цивільно-правовій відповідальності перевізника як одного із способів захисту прав пасажира. Визначено поняття та правову природу, надано цивільно-правову характеристику договору перевезення пасажира, запропоноване його авторське визначення. Охарактеризовано сторони, порядок укладення та зміст договору перевезення пасажира, особливості та наслідки припинення. Визначено правові наслідки порушення договору перевезення пасажира, надано їх правову характеристику та місце в механізмі забезпечення прав пасажира. Сформульовано теоретично обґрунтовані пропозиції щодо вдосконалення цивільного та транспортного законодавства на основі виробленої парадигми правового регулювання перевезень пасажирів за договором, орієнтованого на забезпечення прав пасажира, здійснення ним права на свободу пересування на безпековій основі. На підставі проведеного дослідження розроблено проект Закону України «Про перевезення пасажирів».

Диссертация на соискание научной степени доктора юридических наук по специальности 12.00.03 – гражданское право и гражданский процесс; семейное право; международное частное право. – Национальный университет «Одесская юридическая академия». Одесса, 2021. Диссертация является первым в отечественной науке гражданского права комплексным исследованием теоретических и практических проблем обеспечения прав пассажира по договору перевозки пассажира в условиях глобализации и евроинтеграционных процессов, на основании которого разработана концепция их гражданско-правового обеспечения. В диссертации определены методологические основы исследования и дана правовая характеристика правового регулирования договорных отношений по перевозке пассажира как одного из способов осуществления права на свободу передвижения, обеспечения прав пассажира в современных цивилизационных условиях. Дана правовая характеристика правоотношений по перевозке пассажира и определена их структура. Аргументирован потребительский характер правоотношения по перевозке пассажира, представительный характер отношений между перевозчиком и другими участниками правоотношений по перевозке пассажира. Дана правовая характеристика 42 правоотношений на основе использования мобильных приложений на основе платформ Uber и BlaBlaCar. Установлены особенности механизма правового регулирования перевозок пассажиров и охарактеризованы его элементы, нормативно-правового и договорного регулирования перевозки пассажира, соотношение актов гражданского, транспортного и потребительского законодательства в регулировании этих отношений и обеспечении прав пассажира. Установлены особенности правового регулирования отношений по перевозке пассажиров в ЕС. Определено правовое положение пассажира как стороны договора и потребителя транспортных услуг в концепте права на безопасность. Определены закрепленные в законодательстве права пассажира, а также права, нуждающиеся в признании и правовой охране. Предложен целостный подход к формированию эффективного механизма обеспечения прав пассажира. Особое внимание уделено гарантиям обеспечения прав пассажира, последствиям нарушения его прав, их гражданско-правовой защиты, гражданско-правовой ответственности перевозчика как одного из способов защиты прав пассажира. Определены понятие, правовая природа, предоставлена гражданско-правовая характеристика договора перевозки пассажира, предложено его авторское определение. Охарактеризованы стороны, порядок заключения и содержание договора перевозки пассажира, особенности и последствия его прекращения. Определены правовые последствия нарушения договора перевозки пассажира, их правовая характеристика и место в механизме обеспечения прав пассажира. Сформулировано теоретически обоснованные предложения по совершенствованию гражданского и транспортного законодательства на основе предложенной парадигмы правового регулирования перевозок пассажиров по договору, ориентированного на обеспечение прав пассажира, осуществления им права на свободу передвижения на безопасной основе. На основании проведенного исследования разработан проект Закона Украины «О перевозке пассажиров».

Dissertation for obtaining the degree of Doctor of Law in the specialty 12.00.03 – Civil Law and Civil Procedure; Family law; International Private Law. – National University «Odessa Law Academy». Odessa, 2021. The dissertation is the first in the domestic science of civil law comprehensive research of theoretical and practical problems of passenger rights under the contract of passenger transportation in the context of globalization and European integration processes, on the basis of which the concept of their civil law is developed. The dissertation defines the methodological principles and provides a general description of the legal regulation of contractual relations for the carriage of passengers as one of the ways to exercise the right to freedom of movement, ensuring the rights of passengers in modern civilization. Systematic violations of passengers ‘rights, lack of an effective mechanism for protection of passengers’ rights in accordance with Ukrainian legislation in contrast to the EU, which implements the idea of protection of human rights in all spheres of human life (including transport); the lack of systemic regulatory guarantees for the rights of passengers on all modes of transport – necessitated: a comprehensive study of theoretical and applied problems of legal support for the rights of passengers under the contract of carriage under the laws of Ukraine and the EU; developing a unified approach to solving their problems of ensuring the rights of the passenger on modern ideas of private law. The legal characteristic of legal relations on passenger transportation is given and their structure is defined. The consumer nature of the legal relationship for passenger transportation, the representative nature of the relationship between the carrier and other participants in the legal relationship for passenger transportation are argued. The legal characteristics of legal relations based on the use of mobile applications based on Uber and BlaBlaCar platforms are provided. The peculiarities of the mechanism of legal regulation of passenger transportation are established and the characteristics of its elements, normative-legal and contractual regulation of passenger transportation, ratio of acts of civil, transport and consumer legislation in regulation of these relations and provision of passenger rights are given. The specifics of the mechanism of legal regulation of passenger transportation and ensuring the rights of passengers and the effectiveness of this mechanism are determined; the tendencies caused by transformation of legal system in the conditions of globalization processes are defined. It is argued that the carriage of a passenger under a contract of carriage is not only a contractual obligation but also a way for the passenger to exercise the right to freedom of movement. This requires balanced approaches to the legal protection of the rights of a passenger who is a “weak” party to the contract. It is determined that the transport legislation of Ukraine in the field of protection of passenger rights in the light of modern civilizational achievements does not meet the needs of passengers (in the context of human rights, passenger rights). Transport legislation focuses more on the interests of the carrier than the passenger. Peculiarities of legal regulation of relations on passenger transportation in the EU are established. The legal status of the passenger as a party to the contract and the consumer of transport services in the concept of the right to safety is determined. 44 The rights of the passenger that are recognized and those that need recognition and legal protection are defined. A holistic approach to the formation of an effective mechanism for ensuring passenger rights is proposed. Particular attention is paid to guarantees of ensuring the rights of the passenger, the consequences of violation of his rights, their civil protection, civil liability of the carrier as one of the ways to protect the rights of the passenger. The concept and legal nature are defined, the civil-legal characteristic of the contract of transportation of the passenger is given, its author’s definition is offered. The author’s definition of the contract of transportation of the passenger, which is offered to fix in h. 1 Art. 910 of the Civil Code of Ukraine in the following wording: «1. Under the contract of carriage of a passenger, one party (carrier) undertakes to transport the other party (passenger) to the destination or to move it along a certain route in accordance with the conditions specified by the parties, established by transport codes and statutes, rules of passenger transportation, in case of baggage delivery – also to deliver luggage to the destination and hand it over to the person who has the right to receive luggage, and the passenger undertakes to pay the fare, and in case of baggage delivery – also for its delivery». The parties, the procedure for concluding and the content of the passenger transportation contract, the features and consequences of termination are determined. The legal consequences of the violation of the passenger transportation contract are determined, their legal characteristics and place in the mechanism of ensuring the rights of the passenger are given. Theoretically substantiated proposals for improving civil and transport legislation on the basis of the developed paradigm of legal regulation of passenger transportation under the contract, focused on ensuring the rights of the passenger, the exercise of the right to freedom of movement on a security basis. On the basis of the conducted research the project of the Law of Ukraine “About transportation of passengers” is developed.
дис. ... докт. юрид. наук: 12.00.03
Самойленко Г.В. Договір перевезення пасажира: теорія та практика забезпечення прав пасажира: дис. ... д-ра юрид. наук: 12.00.03 / Самойленко Георгій Валерійович. Одеса, 2021. 553 с.
Keywords: перевезення; договір перевезення; акти ЄС про договори перевезення; законодавство України про договори перевезення; пасажир; споживач транспортної послуги; перевізник; права пасажира; право пасажира на безпеку; механізм забезпечення прав пасажира; правові наслідки порушення договору перевезення пасажира; перевозка; договор перевозки; акты ЕС о договорах перевозки; законодательство Украины о договорах перевозки; пассажир; потребитель транспортной услуги; перевозчик; права пассажира; право пассажира на безопасность; механизм обеспечения прав пассажира; правовые последствия нарушения договора перевозки пассажира; carriage; contract of carriage; EU acts on carriage contracts; Ukrainian legislation on carriage contracts; passenger; consumer of transport services; carrier; passenger rights; passenger’s right to safety; mechanism for ensuring passenger rights; legal consequences of violation of the passenger carriage agreement